2003
DOI: 10.1097/01.asn.0000054495.96193.bf
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effect of ACE Inhibition and Angiotensin II Receptor Blockade in Type I Diabetic Patients with Diabetic Nephropathy

Abstract: Abstract. Albuminuria and hypertension are predictors of poor renal and cardiovascular outcome in diabetic patients. This study tested whether dual blockade of the renin-angiotensin system (RAS) with both an angiotensin-converting enzyme (ACE) inhibitor (ACE-I) and an Angiotensin-II receptor blocker (ARB) is superior to either drug alone in type I diabetic patients with diabetic nephropathy (DN). A randomized double-blind crossover trial was performed with 8-wk treatment with placebo, 20 mg of benazepril once … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
148
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 194 publications
(159 citation statements)
references
References 48 publications
8
148
3
Order By: Relevance
“…The improvement of BP control by using antihypertensive agents, such as ACE inhibitors or ARBs, has also been reported in previous studies (2,3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A significant increase in the prescription of ARBs was observed in 2003 compared with 1996 in RD patients.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…The improvement of BP control by using antihypertensive agents, such as ACE inhibitors or ARBs, has also been reported in previous studies (2,3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25). A significant increase in the prescription of ARBs was observed in 2003 compared with 1996 in RD patients.…”
Section: Discussionsupporting
confidence: 73%
“…Several studies have suggested that the combined treatment with ACE inhibitors and ARBs may be more renoprotective than treatment with either agent alone (12,(20)(21)(22)24), and, indeed, in some RD patients, the combination of ACE inhibitors and ARBs was also prescribed in the present study. The improvement of BP control by using antihypertensive agents, such as ACE inhibitors or ARBs, has also been reported in previous studies (2,3,(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…The addition of ARB induced a mean reduction in albuminuria of 37% and a reduction in 24-h BP of 8 mmHg SBP (P ϭ 0.11) and 5 mmHg DBP (P Ͻ 0.01). Similar results were reported by the same author in type 1 diabetes in a randomized, double-blind, crossover trial of 18 patients who had albuminuria Ͼ300 mg/24 h and received 8 wk of placebo, 20 mg of benazepril, or 80 mg of valsartan and the combination (20 mg ϩ 80 mg) in a random order (29). Treatment with benazepril, valsartan, or dual blockade significantly reduced albuminuria and BP compared with placebo.…”
Section: Combined Treatment With Acei and Arbsupporting
confidence: 82%
“…All strategies reduce proteinuria compared with single-agent therapy (5)(6)(7)(8)(9)(10)(11), but hyperkalemia is a risk (12,13). Regimens including an ACE inhibitor and ARB or either drug and DRI are not recommended not only because of the risk of hyperkalemia but also because of renal failure and hypotension, which were seen in large clinical trials (14,15).…”
Section: Introductionmentioning
confidence: 99%